The career arts : making the most of college, credentials, and connections - Wildavsky, Ben (Princeton University Press, 2024)
"Young people coming out of high school today can expect to hold many jobs over the course of their lives, which is why they need a range of essential skills. The Career Arts provides a corrective to the widespread and misleading notion that there is a direct trade-off between going to college and acquiring practical job skills. Ben Wildavsky cuts through the noise and anxiety surrounding this issue to offer sensible, clear-eyed guidance for anyone who is making decisions about education and career preparation with a view to getting ahead in the workforce. Drawing on evidence-based research, illuminating case studies, and in-depth interviews, Wildavsky shares the most vital lessons of what he calls the career arts, which include cultivating a mix of broad and targeted skills, taking advantage of employer-funded education benefits, and preparing for the world as it is, not as you wish it could be. He explains why college remains the gold standard of credentials, and presents the most promising high-quality supplements and alternatives to college that can help learners combine general and job-specific skills. He shows how building social capital is also critical to success, particularly for disadvantaged students. An invaluable guidebook for students, parents, counselors, and educators, The Career Arts reveals why college education and job preparation are not either-or propositions, and identifies the blend of education and networking needed to support real-world career aspirations"--